Fulfillment of The Elements of The Article Regarding Suspension of The Manufacturer or Producer of "Over Dimensional" Vehicles in The Jurisdiction of The Lamongan Resort Police - Susilo Aji Sujatmiko (Jurnal Ilmu Multidisiplin, 2025)
Although the Traffic and Goods Transportation Law and the Criminal Code have regulated ODOL cases, in the problems that occur in the field, there are still many parties who drive vehicles or drivers who are subject to criminal sanctions for ODOL, which should also impose responsibility and criminal sanctions on the owners or manufacturers of the vehicles and goods being transported. Although it is undeniable that the drivers or drivers of the vehicles are also guilty of their actions in carrying ODOL vehicles, on the other hand they are only carrying out the duties of their superiors, both from the owner or manufacturer of the vehicle and goods. And in this case, it only harms one party, namely the goods transport driver, because in the regulations that regulate and the reality in the field, all the burden of error is only borne by the driver of the vehicle and clarity regarding action against the owner or manufacturer of the vehicle and goods for vehicles carried by goods transport drivers on the orders or orders of the owner or manufacturer of the vehicle or goods is not yet clear. The research method used is empirical law. The results of this study are that the application of Article 55 of the Criminal Code to ensnare ODOL vehicle manufacturers still faces significant challenges in proving the element of involvement. The construction of criminal liability involving manufacturers requires complex proof of the causal relationship between company policy and vehicle modification actions. In the case of CV. Transindo's Source of Results , although there are strong indications of the involvement of company leaders in giving modification orders, formal proof is often hampered by minimal documentation and the complexity of the chain of command